2017
DOI: 10.1097/md.0000000000007681
|View full text |Cite
|
Sign up to set email alerts
|

Changes in ischemia-modified albumin in myocardial toxicity induced by anthracycline and docetaxel chemotherapy

Abstract: This study aims to evaluate differences in myocardial toxicity induced by different chemotherapy regimens. Patients were divided into 2 groups: epirubicin (EPI) combined with cyclophosphamide (EC) group and docetaxel combined with cyclophosphamide (TC) group. Changes in electrocardiograph (ECG) and ischemia-modified albumin (IMA) were determined pre- and 1, 3, and 6 courses of postchemotherapy. After the first course of chemotherapy, there was no significant difference in ECG and abnormal IMA incidence rates b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Albumin was modified by the hydroxyl radical leading to the formation of IMA. It was pointed out for the first time that the formation of IMA is directly related to this production of active oxidation species and confirmed that hydroxyl radicals play an important role in the formation of IMA (25). It was concluded that serum IMA amounts were elevated in patients with breast cancer (26).…”
Section: Discussionmentioning
confidence: 91%
“…Albumin was modified by the hydroxyl radical leading to the formation of IMA. It was pointed out for the first time that the formation of IMA is directly related to this production of active oxidation species and confirmed that hydroxyl radicals play an important role in the formation of IMA (25). It was concluded that serum IMA amounts were elevated in patients with breast cancer (26).…”
Section: Discussionmentioning
confidence: 91%
“…DCM, which results from chemotherapy with anthracycline antibiotics, was also accompanied by an increase in IMA, and serum IMA levels correlated positively with the cumulative dose of an anthracycline antibiotic [90]. It was noted that epirubicin treatment leads to a more significant increase in IMA levels over time compared with doxorubicin treatment (195:6 ± 81:3 and 140:1 ± 14:8 U/mL, respectively) [91].…”
Section: Disease Markersmentioning
confidence: 97%
“…Some drugs are widely used in cancer therapy such as doxorubicin which is one of the commonly used drugs because it's fighting various types of tumor including hematological cancers, sarcomas and carcinomas [1,2,3]. Regardless of its efficacy in fighting a variety of tumors, doxorubicin had side effects on several organs including liver causing high toxicity [4,5].…”
Section: Introductionmentioning
confidence: 99%